STRATEGY OF RELIGIOUS COUNSELORS IN PREVENTING EARLY MARRIAGE THROUGH MENTAL HEALTH LITERACY - Kartini Kartini; Artiyanto Artiyanto; Depi Putri; Heru Prasetyo (Universitas Muhammadiyah Lampung, 2026)
South Sumatra recorded an 8.09 percent rate of underage marriages, ranking 10th highest out of 38 provinces in Indonesia. Although early marriage is permitted according to religious law, it can have impacts on both biological and psychological aspects. The purpose of this research is to understand the strategies of religious counselors in preventing early marriage thru mental health literacy. The research method uses a qualitative approach, with data sources obtained thru observation, interviews, and documentation. Data analysis techniques include reduction, presentation, and conclusion drawing. The research results show the strategies implemented by religious counselors, which include enforcing regulations, traditional and digital-based education, and then integrating mental health materials into activities at all levels of society. This research emphasizes that the strategies employed by religious counselors have helped raise awareness among the community and adolescents specifically about the dangers of child marriage and the psychological impacts it causes.